Applications of Maxwell's Equations - Cochran, John F.; Heinrich, Bretislav; Open Textbook Library (Open Textbook Library, 2004)
This book was developed at Simon Fraser University for an upper-level physics course. Along with a careful exposition of electricity and magnetism, it devotes a chapter to ferromagnets. According to the course description, the topics covered were "electromagnetics, magnetostatics, waves, transmission lines, wave guides,antennas, and radiating systems."
1 Maxwell's Equations -- 2 Electrostatic Field (I) -- 3 Electrostatic Field (II) -- 4 The Magnetostatic Field (I) -- 5 The Magnetostatic Field (II) -- 6 Ferromagnetism -- 7 Time Dependent Electromagnetic Fields -- 8 E.M. Fields and Energy Flow -- 9 Plane Waves (I) -- 10 Plane Waves (II) -- 11 Transmission Lines -- 12 Waveguides
In English.
Description based on online resource
Keywords: Physics -- Textbooks